أهمية اصلاح الجباية المحلية في سبيل تحقيق التنمية المحلية - دلالجة, سارة (جامعة الوادي - University of Eloued, 2017)
تعتبر الجباية المحلية من أهم مصادر التمويل بحيث تشكل القسم الأكبر من ميزانيات الجماعات المحلية، وذلك باعتبارها موردا هاما تستخدمه هذه الأخيرة قصد إشباع حاجات المواطنين وضمان السير الحسن للمرافق العمومية، وبالتالي دفع عجلة التنمية، وبما أن الجباية تمثل أهم مورد من موارد الجماعات المحلية، كان على الدولة مواصلة سلسلة الإصلاحات الرامية للنهوض بها وإعادة الاعتبار لها، لما لها من دور في تحقيق التنمية، على اعتبار أن هذه الأخيرة تعتمد بالدرجة الأولى على التمويل المحلي. تهدف هذه الدراسة إلى إبراز أهمية الاصلاحات الجبائية المحلية في تحقيق التنمية من خلال تشخيص هيكل الجباية المحلية والتعرف على مختلف الاصلاحات الجبائية. The importance of local tax reform to achieve local development Local collectivities is one of the most important sources of funding, which constitutes the largest part of the budgets of the local communities, as an important resource used by the latter to satisfy the needs of citizens and ensure the good conduct of public utilities and thus promote development. The State should continue the series of reforms aimed at promoting and rehabilitating them, because of their role in achieving development, since the latter depends primarily on domestic financing. The aim of this study is to highlight the importance of local tax reforms in achieving development by diagnosing the structure of local taxation and identifying the various tax reforms.
The Importance Of Local Tax Reform To Achieve Local Development
مقال
Keywords: الجباية المحلية، الجماعات المحلية، الاصلاحات الجبائية المحلية، التنمية المحلية